PERHITUNGAN BIAYA TUNDAAN LALU LINTAS DI JALAN PANGERAN SURYANATA KOTA SAMARINDA - ASMIR, MARICA (KURVA S JURNAL MAHASISWA, 2013)
Growth and development of the city led to an increase in population activities. Increased activity of this population can be seen from the change in land use pattern of the city. Land use within a city is dinamisSalah the road with a high intensity activities in the city of Samarinda is Suryanata Prince Street. This road is part of a network of roads linking the city of Samarinda with sub-center at the Ulu Ulu located in Samarinda District. Traffic delay cost is the difference between a trip to the delay in travel expenses without delay or stable condition. So to know the cost of delay, must be known in advance of the travel expenses and the cost of a trip to tundaaan with stable conditions. Travel costs obtained from the multiplication of the number of vehicles, travel time, and the sum of Vehicle Operating Costs with the value of time. From the results of the calculation, the cost of travel in stable condition in the Prince Suryanata streets of Samarinda is the sum of Rp. 10766.00 / km / vehicle. And based on the calculation of the cost of travel in the delay condition is Rp. 17379.00 / km / vehicle so that the difference between the cost of delay to the steady state condition is Rp. 6613.00 / km / vehicle. This result suggests that the views of the major costs incurred by road users, caused considerable losses, and will increase if it is associated with the loss due to air pollution and noise pollution on public health and the environment